Challenges facing auditors in the practice of internal audit: The case of Morogoro District council. - Kapula Nunkongea (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfillment of the Requirements for Award of the Degree of Master of Science in Accounting and Finance (MSc. A&F) of Mzumbe University